The role of the influence of social avoidance and distancing on the predisposition to anxiety disorders during the covid-19 pandemic - Avramchuk, Oleksandr (Psychosomatic Medicine and General Practice, 2021)
Background. Quarantine restrictions during the COVID-19 pandemic have become an important trigger for psycho-emotional distress and the manifestation of vulnerability to mental health problems. Physical ("social") distancing, aimed at preventing the spread of COVID-19, has allowed people with a history of common mental health problems (such as depression, generalized anxiety disorder, or social phobia) to receive some short-term relief by giving rational justification for the maladaptive strategies of behavioral or cognitive avoidance of trigger situations or life circumstances. However, it is assumed that the avoidance of social interaction or situations may contribute to the masking of persistent functional disorders associated with the level of social anxiety in particular. At the same time, the denial of one’s own needs and the uncertainty of the future in the context of pandemics and quarantine restrictions will affect vulnerability to anxiety disorders, which may increase after quarantine restrictions and the need to return to everyday life. Analysis of the role of social avoidance and distancing during the pandemic will expand the understanding of the mechanisms of vulnerability to psychosocial dysfunction for anxiety disorders. The results can help develop recommendations for self-help and psycho-correctional programs aimed at psychoeducation and prevention of common mental health problems. Objective. Investigate the features of psycho-emotional discomfort associated with avoiding experience as a factor in vulnerability to anxiety disorders in a pandemic setting. Materials and methods. The study group included 242 individuals who complained of significant psycho-emotional distress related to social restrictions due to quarantine conditions and/or avoidance of social contacts due to anxiety (including anxiety before negative evaluation and condemnation, health concerns, uncertainty, etc.). Age distribution from 18 to 35 years (M = 24.3; SD = 4.93), mostly female - 66.94% (n = 162). The main sample was 126 subjects, and 116 people formed a control. Diagnostic interviews with The MINI: International Neuropsychiatric Interview, self-questionnaires, and scales from complex IAPT and SCL-90-R were used to study the pathopsychological symptoms, were conducted as part of the screening of the mental state. AAQ-II self-questionnaire was assessed for experiential avoidance. Results. We studied the relationship between strategies for coping with distress by experiential avoiding under quarantine restrictions and psycho-emotional discomfort in current life situations and vulnerability to anxiety disorders during interviews. The study found that quarantine restrictions can be seen as a factor in general vulnerability to the anxiety response. At the same time, avoidance of the corrective experience under quarantine restrictions increases the manifestation or risk of recurrence of more specific anxiety disorders. Considering experiential avoidance (as inflexible use of maladaptive strategies to regulate emotions and somatic sensations) associated with uncertainty and the duration of social restrictions significantly contributes to pathogenetic cycles of anxiety disorders. Additional vulnerabilities in the combined regression model were male gender, age-range 24-35 years, and the presence of one or more common mental disorders in anamnesis. The results are consistent with the indirect relationship between experiential avoidance, symptomatic distress, and daily and work activities. The obtained results have the prospect of further developments, particularly in developing recommendations for psychosocial support and prevention of common anxiety disorders in the context of global change.